PERENCANAAN DAN PENYELENGARAAN EVENT SEMINAR NASIONAL STARTUP DI INDUSTRI KREATIF ZAMAN NOW BERBASIS DIGITAL BUSINESS - Teguh Widodo (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
Abstract: This seminar is an activity related to pioneering company that nowday runs its business in the creative industries world through a growing digital business. The specific objectives of the research are to know the technical aspects of the work donational implementation, to determine the required human resource, to determine job specification and job description committee, to determine the criteria of the resource, motivate the working team in the organization, know the descriptive reports and financial reports of human and operational aspects, to find out the constraints that occur from the beginning of preparation to the implementation of the seminar, to find out how the solution of the constraints that occur from the beginning of preparation to the implementation of the seminar. The methods used in planning and organizing this seminar consist of project preparatory plans, project implementation plans, project completion plans and project reporting plans. The result of the research shows that the initial plan that is the determination of activity specification and job description and looking for experienced and expert source. In the implementation of motivation given the extrinsic motivation, intrinsic and needs continued run the agenda of the event. While the form of supervision that is preventive and repressive. Project reporting consists of implementation reports and financial reports